Myb transcription factors and light regulate sporulation in the oomycete Phytophthora infestans. - Qijun Xiang; Howard S Judelson (PLoS ONE)
Life cycle progression in eukaryotic microbes is often influenced by environment. In the oomycete Phytophthora infestans, which causes late blight on potato and tomato, sporangia have been reported to form mostly at night. By growing P. infestans under different light regimes at constant temperature and humidity, we show that light contributes to the natural pattern of sporulation by delaying sporulation until the following dark period. However, illumination does not permanently block sporulation or strongly affect the total number of sporangia that ultimately form. Based on measurements of sporulation-induced genes such as those encoding protein kinase Pks1 and Myb transcription factors Myb2R1 and Myb2R3, it appears that most spore-associated transcripts start to rise four to eight hours before sporangia appear. Their mRNA levels oscillate with the light/dark cycle and increase with the amount of sporangia. An exception to this pattern of expression is Myb2R4, which is induced several hours before the other genes and declines after cultures start to sporulate. Transformants over-expressing Myb2R4 produce twice the number of sporangia and ten-fold higher levels of Myb2R1 mRNA than wild-type, and chromatin immunoprecipitation showed that Myb2R4 binds the Myb2R1 promoter in vivo. Myb2R4 thus appears to be an early regulator of sporulation. We attempted to silence eight Myb genes by DNA-directed RNAi, but succeeded only with Myb2R3, which resulted in suppressed sporulation. Ectopic expression studies of seven Myb genes revealed that over-expression frequently impaired vegetative growth, and in the case of Myb3R6 interfered with sporangia dormancy. We observed that the degree of silencing induced by a hairpin construct was correlated with its copy number, and ectopic expression was often unstable due to epigenetic silencing and transgene excision.